A comparative description of the roach (Rutilus rutilus; Cypriniformes; Actinopterygii) from the Nura and Lena Rivers (Eurasian Journal of Ecology, 2016)
Examination of morphological variability of fishes in different living conditions has importance for development of system of ichthyological monitoring. With that purpose an comparative examination of roach Rutilus rutilus (Linnaeus,1758) from the Nura and Lena Rivers was provided. 9 counted and 28 measured characteristics had been investigated. Differences in many of characteristics revealed. Significant variability of counted characteristics and shift of metabolism to the adiposis reflect intensive anthropogenic impact to the roach in the Nura River. The obtained data show wide adaptivity of the roach.
Keywords: morphobiology; roach; ecomorphology; characteristic; variability; anthropogenic